PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN E-LEARNING TERHADAP KREATIVITAS DAN HASIL BELAJAR MATEMATIKA (FPMIPA IKIP PGRI Bali, 2019)
This study aimed to assess the effect of Problem Based Learning model with e-learning to creativity and learning result of mathematics on tenth grade student of SMK Negeri 4 Denpasar on academic year 2017/2018. This type of research was quasi experiment, using non equivalent posttest-only control group design. The population in this study were the student of tenth grade PH of SMK Negeri 4 Denpasar with 4 classes (144 students). Using multistage random sampling technique, 2 classes were obtained as sample, wich is tenth grade PH 3 (36 students) as control group and tenth grade PH 1 (36 students) as experiment group. The data obtained of learning creativity score using questionnaire and mathematics learning result score using test method. Data analysis using MANOVA with SPSS 24.0 for windows. Based on the obtained result of hypothesis testing: 1) there were significant difference in creativity of student who joined the problem based learning model with e-learning with the student who joined the conventional learning model, by value (sig.) ≤ α (0,001 ≤ 0,05), 2) there were significant difference in mathematics learning result of student who joined the problem based learning model with e-learning with the student who joined the conventional learning model, by value (sig.) ≤ α (0,001 ≤ 0,05), and 3) there were simultaneous difference in creativity and mathematics learning result of student who joined the problem based learning model with e-learning with the student who joined the conventional learning model, by value (sig.) ≤ α (0,001 ≤ 0,05). So, there are an effect of problem based learning model with e-learning to students's mathematics learning creativity and result.